2018
DOI: 10.1002/jbio.201700245
|View full text |Cite
|
Sign up to set email alerts
|

Label‐free imaging and spectroscopy for early detection of cervical cancer

Abstract: The label-free imaging and spectroscopy method was studied on cervical unstained tissue sections obtained from 36 patients. The native fluorescence spectra of tissues are analyzed by the optical redox ratio (ORR), which is defined as fluorescence intensity ratio between NADH and FAD, and indicates the metabolism change with the cancer development. The ORRs of normal tissues are consistently higher than those of precancer or cancerous tissues. A criterion line of ORR at 5.0 can be used to discriminate cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…In this study, the group of adenomyosis patients revealed similar feature as CIN and cervical cancer groups reported previously. 7 Therefore, the result may imply that uterine adenomyosis growth is more invasive compared with leiomyomas, which is consistent with clinical manifestations.…”
Section: Flim Images Of Cervical Tissuesupporting
confidence: 58%
See 1 more Smart Citation
“…In this study, the group of adenomyosis patients revealed similar feature as CIN and cervical cancer groups reported previously. 7 Therefore, the result may imply that uterine adenomyosis growth is more invasive compared with leiomyomas, which is consistent with clinical manifestations.…”
Section: Flim Images Of Cervical Tissuesupporting
confidence: 58%
“…However, biochemical change occurs when the cellular metabolism becomes abnormal in the case of rapid cell division, which occurs before morphological changes become apparent. 7,8 That means optical techniques have the great potential to detect malignancies or precancer much earlier than traditional histopathology.…”
Section: Introductionmentioning
confidence: 99%
“…When FLIM images were collected with a 532 nm long-pass filter for FAD, the signals of PpIX could be detected. But in our previous work, the fluorescence emission of PpIX at around 620 nm for the cervical tissue samples was very weak [45] and the effect of PpIX signals in cervical tissues is little.…”
Section: Flim Experimental Setupmentioning
confidence: 72%
“…The clinical applications of optical redox ratios, which can be calculated as FAD/[NAD(P)H + FAD], for oral and cervical cancer diagnosis have been discussed [ 26 , 27 ]. However, due to the low quantum yield of NAD(P)H and FAD, the intensity-based method relying on optical redox ratios, is not as sensitive as we expect because of the background fluorescence interference.…”
Section: Flim Combined With Nad(p)h For Cancer Metabolism Monitoringmentioning
confidence: 99%